Current status of intestinal parasitic infections among inhabitants of the Ghazni and Parwan provinces, Afghanistan - Korzeniewski, Krzysztof; Chung, Won Chin; Augustynowicz, Alina; Lass, Anna; Ik, Kim Jong (Family Medicine & Primary Care Review, 2017)
Background. The prevalence rates of food- and waterborne parasitic infections in Afghanistan are unknown. Cases of invasive diseases found in Afghans are rarely laboratory-confirmed. Objectives . The aim of the study was to present the current status of intestinal parasitic infections in Afghan inhabitants on the example of patients hospitalized in two healthcare facilities in eastern Afghanistan. Material and methods . Fecal samples were collected from 548 patients (children aged 1–17 years and adults) with internal complaints, treated in Ghazni Provincial Hospital (Afghan civilian medical center, Ghazni province, 180 south-west of Kabul) and in Bagram Korean Hospital (Korean military medical center for Afghan patients, Parwan province, 60 km north of Kabul) between 2013 and 2014. One to three stool specimens from Afghan patients were fixed in 10% formalin, transported to the Military Institute of Medicine in Poland and tested by light microscopy using three diagnostic methods (direct smear in Lugol’s solution, decantation in distilled water and Fülleborn’s flotation). Results . Intestinal parasites were found in 144/386 of tested patients from the Ghazni province (37.3% infected, mainly with Ascaris lumbricoides , Giardia intestinalis , Hymenolepis nana ) and in 49/162 patients from the Parwan province (30.2% infected, mainly with G. intestinalis , A. lumbricoides , H. nana ). Conclusions . The rates of intestinal parasitic infections among Afghans are high. The wide range of the detected parasites (protozoa, nematodes, cestodes) should result in the introduction of general screening to be conducted regularly among inhabitants of Afghanistan and the application of targeted antiparasitic chemotherapy aiming to eliminate intestinal helminths and protozoa from the local community.